2023
DOI: 10.1093/jsxmed/qdad061.003
|View full text |Cite
|
Sign up to set email alerts
|

(003) The Impact of Gender Affirming Mastectomy on the Sexual Health and Satisfaction of Trans Patients

Abstract: Introduction Gender-affirming mastectomy (GAM) is the most commonly performed gender-affirming surgery. Unfortunately, many areas of sexual health for transmasculine people are understudied. In particular, there are few studies that assess how chest and nipple stimulation, or lack of sensation, affect the sexual health and satisfaction of trans patients after GAM. Objective This study aims to 1) assess the importance of chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A survey of transmasculine patients conducted by Song et al found that nipple sensation was important to 76% of the respondents. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of transmasculine patients conducted by Song et al found that nipple sensation was important to 76% of the respondents. 13 …”
Section: Introductionmentioning
confidence: 99%
“…A survey of transmasculine patients conducted by Song et al found that nipple sensation was important to 76% of the respondents. 13 Advances in peripheral nerve surgery have allowed for the pioneering of new strategies to neurotize the chest during gender-affirming mastectomy. 14 Rochlin et al and Gfrerer et al describe techniques that use either direct coaptation or an allograft interposition to reinnervate the NAC with the lateral cutaneous branches of the intercostal nerves preserved during dissection.…”
mentioning
confidence: 99%